1986
DOI: 10.1152/ajpendo.1986.250.1.e100
|View full text |Cite
|
Sign up to set email alerts
|

Rate-limiting steps for insulin-mediated glucose uptake into perfused rat hindlimb

Abstract: To determine the glucose and insulin concentrations at which glucose transport is rate limiting for insulin-mediated glucose uptake and metabolism in muscle, glucose clearance was determined in the presence of glucose concentrations ranging from trace to 20 mM and in the absence or presence of insulin in the perfused rat hindlimb. In the absence of insulin and at submaximally stimulating insulin concentrations glucose clearance was constant up to 7 mM glucose and then decreased as the glucose concentration was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
2
3

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 15 publications
6
56
2
3
Order By: Relevance
“…The finding that the defect in glucose phosphorylation exceeds that of inward glucose transport is consistent with previous studies from our laboratory that have demonstrated a severe defect in insulin-stimulated muscle hexokinase II activity, mRNA levels, and protein content (37,40,48,63,64). This observation is also consistent with prior studies demonstrating that, under insulin-stimulated conditions, post-glucose transport defects can be rate limiting for intracellular glucose metabolism (10,29,38,42,44,47,49,69). However, it should be emphasized that, even if the defect in hexokinase II were corrected, a severe defect in glucose transport most likely would remain (11) and become rate limiting.…”
Section: Discussionsupporting
confidence: 92%
“…The finding that the defect in glucose phosphorylation exceeds that of inward glucose transport is consistent with previous studies from our laboratory that have demonstrated a severe defect in insulin-stimulated muscle hexokinase II activity, mRNA levels, and protein content (37,40,48,63,64). This observation is also consistent with prior studies demonstrating that, under insulin-stimulated conditions, post-glucose transport defects can be rate limiting for intracellular glucose metabolism (10,29,38,42,44,47,49,69). However, it should be emphasized that, even if the defect in hexokinase II were corrected, a severe defect in glucose transport most likely would remain (11) and become rate limiting.…”
Section: Discussionsupporting
confidence: 92%
“…Decreased insulin-stimulated glucose uptake is a characteristic of insulin resistance in obesity and diabetes (46) and defects in the glucose transport system could represent a significant contribution to the mechanisms of insulin resistance in liver and muscle (47,48). The obese Zucker rat does not normally develop overt diabetes and is a better model of impaired glucose tolerance than diabetes (21).…”
Section: Discussionmentioning
confidence: 99%
“…In insulin-sensitive tissues, insulin stimulates glucose transport by translocation of glucose transporters to the plasma membrane from a large intracellular pool (see Cushman and Simpson 1985). The reduction in glucose uptake by hind limb muscle in the last period of infusion of insulin can be explained by mechanisms suggested by Kubo and Foley (1986). These workers considered that at physiological concentrations of glucose, in the presence of insulin concentrations that stimulate maximally, the rate-limiting step for insulin-mediated uptake of glucose and for glucose metabolism in muscle shifts from glucose transport to some step beyond transport.…”
Section: Discussionmentioning
confidence: 99%